Pelatihan budidaya ikan lele pada kolam terpal dengan sistem akuaponik di Desa Harapan, Kecamatan Sungai Apit, Kabupaten Siak, Provinsi Riau - Mulyadi Mulyadi; Niken Ayu Pamukas; Adelina Adelina; Iesje Lukistyowati; Dessy Yoswati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Most of the Kampung Harapan residents are farmers, namely farming corn, sweet potatoes, chilli, fruit, vegetables (such as spinach and kale) and fish farming. This village is prospective to be used as rearing sites for aquaponic systems. Aquaponic cultivation technology can be developed in limited area and water, and it also can increase business efficiency through the utilization of nutrients from the uneaten fish meal and the metabolism wastes of fish for vegetables, so it could be able to produce fish and vegetables optimally on narrow land and limited water sources, including in urban areas. Through the fish rearing with aquaponic systems, fish farmers will get two advantages in one production stage. This activity was carried out through discussion and practice, which the activity took place in the village office and in the home yard of the fish farmer group in Harapan Village. Extension activities involve fish farmers, plantation farmers and several students. The results of the activities showed that skills and knowledge of fish farmers increase regarding aquaponics fish farming and making pellets mix with gingger. Plastic fish ponds as a pilot project produce high yields of catfish and leafy vegetables, so it can be an alternative income for fish farmers.